Atlas of human infectious diseases - Wertheim, Heiman F. L.; Horby, Peter; Woodall, John P. (Hoboken : John Wiley & Sons, 2012)
The Atlas of Human Infectious Diseases provides a much needed practical and visual overview of the current distribution and determinants of major infectious diseases of humans. The comprehensive full-color maps show at a glance the areas with reported infections and outbreaks, and are accompanied by a concise summary of key information on the infectious agent and its clinical and epidemiological characteristics. Since infectious diseases are dynamic, the maps are presented in the context of a changing world, and how these changes are influencing the geographical distribution on human infection.
Section 5: Viral Infections 90 Avian influenza (A/H5N1); 91 Barmah Forest & Ross River Virus Disease; 92 Bunyamwera Viral Fever; 93 Bunyavirus Group C Disease; 94 California Group Virus Disease; 95 Chikungunya Fever; 96 Colorado Tick Fever; 97 Crimean-Congo Hemorrhagic Fever; 98 Dengue; 99 Eastern Equine Encephalitis; 100 Ebola and Marburg Virus Disease; 101 Hantaviral Disease, New World; 102 Hantaviral Disease, Old World; 103 Hendra and Nipah Virus; 104 Hepatitis A; 105 Hepatitis B; 106 Hepatitis C; 107 Hepatitis E; 108 Human Immunodeficiency Virus; 109 Human T-Lymphotropic Virus 110 Japanese Encephalitis.
Includes bibliographical references and index.
Print version record.
Keywords: Communicable diseases -- Atlases; Communicable Diseases; Parasitic Diseases; Topography, Medical; Virus Diseases; Communicable diseases -- Atlases; Parasitic diseases -- Atlases; Topography, Medical -- Atlases; Virus diseases -- Atlases; Medicine; HEALTH & FITNESS -- Diseases -- Contagious; MEDICAL -- Infectious Diseases; Communicable diseases; Atlases; Electronic books; Atlases